IDENTIFYING SUBJECTIVE VALUE IN WOMEN’S COLLEGE GOLF RECRUITING REGARDLESS OF SOCIO-ECONOMIC CLASS - Allred, Victoria (East Carolina University, 2018)
College athletics have grown into a major industry and athletic departments are pushing coaches to recruit the top talent. To recruit golfers, college coaches depend on multiple ranking systems. These systems are bias towards more expensive, national tournaments over inexpensive, state tournaments. In response, players who come from a lower socio-economic class will have fewer financial aid opportunities than someone from a higher economic class. Analyzing junior girls’ golf statistics, has led to the creation of an objective methodology to compare golfers without regard to socio-economic imbalances.
Keywords: sports economics; golf; golf statistics